Disappearing reeds on Chongming Island: An environmental microhistory of Chinese eco-development. (March 2022) - Xie, Linjun; Mauch, Christof; Tan-Mullins, May; Cheshmehzangi, Ali
This paper critically examines current ecological development planning and practice in China through an environmental microhistory approach. By tracing the gradual disappearance of an indigenous plant – the common reed ( Phragmites australis ) – on Chongming Island in Shanghai, which is known for the grand Eco-Islands development plan, this paper reveals the paradox of ecological destruction through eco-development in China. Based on data collected from archives, through oral history and through on-site fieldwork, we have reconstructed and analysed the transformation of Chongming Island's reed ecology over time. Our research documents the historical importance of reeds to Chongming culture and identity. The transformation of the reed landscape mirrors, we argue, broader environmental and social transformations on the island. The near extinction of the once abundant reed in the coastal wetlands due to massive land reclamation projects for the purpose of industrialisation and urbanisation is a reflection of the prevailing pursuit for economic growth. Land reclamation projects in the early 2000s were facilitated by the planting of an invasive grass that replaced reeds and other native wetland plants. Ironically, the invasive grass served to legitimise continuous land reclamation as part of Chongming's eco-development. Moreover, reeds that grew by the rivers and constituted a central part of local livelihoods were gradually wiped out as a result of a series of river regulation projects under the eco-development. Our research reveals that the current ecological agenda has privileged modern engineering solutions and aesthetics while largely ignoring local traditional knowledge. The case of Chongming delivers a sobering message that well-intentioned ecological initiatives can in fact have disastrous effects if the local environment, its ecological features, cultural characteristics, and historical and social contexts are not fully considered. Overall, this paper pioneers an environmental microhistory approach in evaluating contemporary urban ecological initiatives and contributes methodological and empirical insights to advance Chinese eco-developments.